Differential modulation of apoptosis sensitivity in CD95 type I and type II cells - Watzl, Carsten; Krammer, Peter H.; Peter, Marcus E. (The journal of biological chemistry, 1999)
We have recently identified two different pathways of CD95-mediated apoptosis (Scaffidi, C., Fulda, S., Srinivasan, A., Feng, L., Friesen, C., Tomaselli, K. J., Debatin, K.-M., Krammer, P. H., and Peter, M. E. (1998) >EMBO J. 17, 1675-1687). CD95-mediated apoptosis in type I cells is initiated by large amounts of active caspase-8 formed at the death-inducing signaling complex (DISC) followed by direct cleavage of caspase-3. In contrast, in type II cells very little DISC and small amounts of active caspase-8 sufficient to induce the apoptogenic activity of mitochondria are formed causing a profound activation of both caspase-8 and caspase-3. Only in type II cells can apoptosis be blocked by overexpressed Bcl-2 or Bcl-xL. We now show that a number of apoptosis-inhibiting or -inducing stimuli only affect apoptosis in type II cells, indicating that they act on the mitochondrial branch of the CD95 pathway. These stimuli include the activation of protein kinase C, which inhibits CD95-mediated apoptosis resulting in a delayed cleavage of BID, and the induction of apoptosis by the ceramide analog C2-ceramide. In addition, we have identified the CD95 high expressing cell line BoeR as a CD95 apoptosis-resistant type II cell that can be sensitized by treatment with cycloheximide without affecting formation of the DISC. This also places the effects of cycloheximide in the mitochondrial branch of the type II CD95 pathway. In contrast, c-FLIP was found to block CD95-mediated apoptosis in both type I and type II cells, because it acts directly at the DISC of both types of cells.
Gesehen am 23.04.2021